2021
DOI: 10.5021/ad.2021.33.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Findings and the Clinicopathologic Correlation of Pigmented Purpuric Dermatosis: A Retrospective Review of 60 Cases

Abstract: Background Pigmented purpuric dermatosis (PPD) is known as a chronic recurrent eruption which usually presents with petechiae and pigmented macules on the lower extremities. Dermoscopy is a noninvasive diagnostic tool in identifying pigmented and vascular lesions, which can also be beneficial in the evaluation of PPD. Objective We aimed to analyze the common dermoscopic characteristics of PPD, and correlate those findings with the histopathologic features. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
4
0
0
Order By: Relevance
“…Dark‐brown pigmentation in the superficial dermis could be seen in the histopathological examination, and although there was no definite evidence for this, it may be due to haemosiderin deposition after the red blood cells are absorbed. In some previous studies, 7 red spots, globules and patches corresponded to extravascular red blood cells, while brown spots and globules corresponded to dermal endophagocytic haemosiderin cells at different stages of pigmented purpura dermatosis, which is consistent with our findings.…”
Section: Reportsupporting
confidence: 93%
See 2 more Smart Citations
“…Dark‐brown pigmentation in the superficial dermis could be seen in the histopathological examination, and although there was no definite evidence for this, it may be due to haemosiderin deposition after the red blood cells are absorbed. In some previous studies, 7 red spots, globules and patches corresponded to extravascular red blood cells, while brown spots and globules corresponded to dermal endophagocytic haemosiderin cells at different stages of pigmented purpura dermatosis, which is consistent with our findings.…”
Section: Reportsupporting
confidence: 93%
“…These structures are often seen in lichen sclerosis 6 and pigmented purpuric dermatosis. 7 In the current study, histopathological examination of LCH in all 15 patients showed varying amounts of extravasation of red blood cells in the superficial dermis, which was highly consistent with the purplishred globules or patches seen under dermoscopy.…”
Section: Reportsupporting
confidence: 82%
See 1 more Smart Citation
“…Being inflammatory purpura,[ 9 ] PPDs are probably the main differential diagnosis for CSVV. Comparing our findings with the established dermoscopic features of PPDs,[ 10 - 13 ] we noted the following,…”
Section: Discussionsupporting
confidence: 76%
“…3 Dermoscopy in PPPD is well documented and coppery red pigmentation and red globules are the commonest findings dermoscopically in large majority of the studies. 5,7,8 In this study, brown pigment network and yellowishbrown globules were present in all 30 patients. These findings were similar to the previous reports and compounds that these patterns are highly characteristic of PPPD.…”
Section: Discussionsupporting
confidence: 51%